The Fate of Indigenous Peoples' Rights Recognition After the Enactment of the National Criminal Code - Sunardi Purwanda; Nurul Asyikeen Binti Abdul Jabar; Rudini Hasyim Rado; Nurul Miqat (Universitas Negeri Semarang, 2024)
This recognition requires further regulation through a Government Regulation and serves as a procedural requirement for being acknowledged as indigenous peoples. The purpose of this article is to provide us an overview of how the recognition requirements for indigenous peoples as outlined in legislation, both before and after the enactment of the Criminal Code. Additionally, it examines the struggles of indigenous peoples in Ecuador, who have organized themselves into indigenous groups to fight for the rights that have been taken away from them. This research employs a statutory approach, a comparative approach, and an interdisciplinary approach in law commonly referred to as socio-legal research. As a result of this, indigenous peoples often find themselves in a weak position relative to the dominant authority of the state. The government needs to provide political recognition affirming that indigenous peoples are equal legal subjects with the state and possess the capacity to act legally to represent their interests as indigenous groups. With the enactment of the National Criminal Code set for 2026, this recognition may pave the way for indigenous peoples to become equal parties when engaging with the state in matters of customary criminal law. Additionally, the indigenous movement in Ecuador serves as a significant point of reflection. Their ability to unite indigenous peoples and nations under a national framework has profoundly influenced the political and legal landscape.